2012
DOI: 10.1103/physrevb.85.045405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unreconstructed and reconstructed polar surface terminations on growth, structure, and magnetic properties of hematite films

Abstract: The effects of polar surface stabilization mechanisms on the film growth, phase composition, surface and interface structure, and magnetic properties are explored for polar (1×1) surfaces under equivalent conditions. This study suggests that in addition to the customary strain, spin, and band-gap engineering, control of surface polarity stabilization could also be important for electronic and magnetic device engineering.Cheung et al.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Such an unusual phase behavior was observed neither in (001) Fe 3 O 4 films on (001) MgO, nor in (111) Fe 3 O 4 films on (111) Pt substrates1819. Recently, Lazarov et al reported the formation of a single Fe 3 O 4 nanolayer on a surface of reconstruction-stabilized (111) MgO substrates in thin films of the hematite phase (α-Fe 2 O 3 )6. On the contrary, when the unreconstructed (111) surface of MgO was hydrogen-stabilized, the magnetite phase was not detected in Fe 2 O 3 thin films 6.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such an unusual phase behavior was observed neither in (001) Fe 3 O 4 films on (001) MgO, nor in (111) Fe 3 O 4 films on (111) Pt substrates1819. Recently, Lazarov et al reported the formation of a single Fe 3 O 4 nanolayer on a surface of reconstruction-stabilized (111) MgO substrates in thin films of the hematite phase (α-Fe 2 O 3 )6. On the contrary, when the unreconstructed (111) surface of MgO was hydrogen-stabilized, the magnetite phase was not detected in Fe 2 O 3 thin films 6.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lazarov et al reported the formation of a single Fe 3 O 4 nanolayer on a surface of reconstruction-stabilized (111) MgO substrates in thin films of the hematite phase (α-Fe 2 O 3 )6. On the contrary, when the unreconstructed (111) surface of MgO was hydrogen-stabilized, the magnetite phase was not detected in Fe 2 O 3 thin films 6. Thus, the polarity of the oxide surface and its reconstruction may play a crucial role in the process of phase stabilization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the thin film forms, the substrates have a pivotal role in the stabilization of the iron oxide phase, modulating the physical properties as well as facilitating the application of iron oxides. For instance, the lattice matching of the substrate with the constituent film is very vital for the epitaxial formation of metastable phase ε-Fe 2 O 3 thin film, modification of physical properties of iron oxide by crafting the interfacial structures utilizing polar and nonpolar substrates, and the choice of conducting substrate which is important to determine the solar conversion performance of α-Fe 2 O 3 -based PEC, etc. Here we divide the review according to the types of substrates used to grow iron oxide: ceramics, polymer, and metal substrates.…”
Section: Role Of Substratesmentioning
confidence: 99%